Testing the Environmental Kuznets Curve Hypothesis Test: A Case Study of BRICS Countries - Prabaswati, Vera Candra; Putri, Phany Ineke (Efficient: Indonesian Journal of Development Economics, 2025)
The world's environmental crisis is a growing concern. Carbon dioxide is the most dominant greenhouse gas causing major climate change and global warming through human activities, including economic activities. This study aims to test the EKC theory in BRICS and the independent variables of exports, Foreign Direct Investment (FDI), and renewable energy consumption. Research method using the Pooled Mean Group method ARDL (1990-2022). The results show that the EKC hypothesis is proven in BRICS and forms an inverted U curve in the long run. Export has a positive effect in the long run. FDI has a positive effect in the long run. Energy consumption has a negative in the long run.